STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN KOMPETENSI SIKAP SOSIAL SISWA DI SMA NEGERI 1 BENAI - Aprilla Tegu Mulia; Wigati Iswandhiari; Ikrima Mailani (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2019)
This study aims to find out the strategies of Islamic Religious and Character Education teachers as well as supporting and inhibiting factors in developing students' social attitude competencies (descriptive study of 2013 curriculum) in Benai 1 High School. Based on the results of data collection by means of observation, interviews and documentation, then the data is analyzed by Data Reduction (data reduction) Presentation of data (data display), Verification (Conclusing Drawing) in the form of concluding sentences. From this research, it can be concluded that the strategy of Islamic Religious Education teachers develop students' social attitude competency (descriptive curriculum study in 2013) at SMA Negeri 1 Benai more by giving examples and giving advice. Giving an example is to always come to school on time, throwing trash in its place and in the form of advice is an invitation or suggestion that students are invited to obey school rules, do not cheat when the test is held, the teacher gives students the responsibility by collecting assignments on time. Keywords: Teacher Strategy, Student Social Attitude Competency